Strengthening of unreinforced masonry: A systematic review of mechanical performance gains and limitations of reinforcement systems - Brito, Isaac Sérgio Araújo de; Lima, Victor Marcelo Estolano de; Oliveira, Tiago Ancelmo de Carvalho Pires de; Rabbani, Emilia Rahnemay Kohlman (National Journal of City Management, 2026)
Objective – To systematically analyze reinforcement techniques applied to unreinforced masonry, focusing on gains in mechanical strength, particularly compressive and shear resistance, as well as on the limitations associated with the different reinforcement systems reported in the scientific literature.Methodology – A Systematic Literature Review was conducted based on a predefined search protocol, clear inclusion and exclusion criteria, and the application of the PRISMA method for study selection. The selected articles were analyzed according to masonry type, reinforcement technique, experimental configuration, percentage gains in strength, and reported limitationsOriginality/Relevance – This study addresses a relevant gap in the literature by providing a comparative and integrated synthesis of mechanical performance gains and technical limitations of the main reinforcement systems applied to unreinforced masonry, supporting a critical assessment of their structural effectiveness and practical applicability.Results – The results indicate that the highest strength gains are predominantly associated with in-plane shear loading, especially for systems based on textile- or fiber-reinforced mortars, such as TRM and FRCM, with increases frequently exceeding two hundred percent. Gains in compressive strength were generally more moderate and mainly related to confinement mechanisms. The most recurrent limitations include performance variability, premature failure at the reinforcement–substrate interface, chemical incompatibility, and restrictions on application in historic masonry.Theoretical/Methodological Contributions – The study consolidates a comparative framework relating mechanical performance and technical limitations of reinforcement systems and highlights the need for more suitable design models for systems based on inorganic matrices.Social and Environmental Contributions – The findings support the selection of reinforcement solutions that are more compatible with existing and historic buildings, contributing to safer, more durable interventions aligned with sustainability and built heritage conservation principles.
Keywords: Unreinforced masonry; Structural strengthening; Shear strength; Systematic literature review